Survey on health management practices followed by Pantja goat keepers in Tarai region of Uttarakhand - J.L. SINGH and C.B. SINGH, B.S. KHADDA, BRIJESH SINGH2 D.V. SINGH, S.K. SINGH (Indian Journal of Animal Production and Management, 2020)
A bench mark survey was conducted to collect the base line information from the Pantja goat rearersregarding various health management practices of goats under field conditions of Udham Singh Nagarand Nainital districts of Tarai region of the Uttarakhand during a period of two year (April, 2015 to March,2017). The results of present study revealed that maximum goat rearers (55.81%) followed vaccinationpractice in the goats while, 44.19 per cent did not adopted this practice. The majorities of goat keepers(70.39%) were well aware towards deworming practices and followed it once or twice in a year. Majorityof goat keepers (61.24%) practiced to control ecto- parasites and among them 52.15 per cent practicedmanual or indigenous traditional practices used for control of ecto- parasites while; remaining 47.85 percent used dusting/ spraying (insecticides) method to control external parasites. Overall 95.04 per cent ofgoat keepers used veterinary/ indigenous traditional practices for the treatment of sick animals. Majorityof the respondents (52.87%) informed that they prefer quacks, followed by (27.13%) trained person likeveterinary doctors/ livestock inspectors for treatment of their sick and injured animals. Overall data showsthat majority of goat keepers (51.94%) reported that availability of veterinary facilities for the treatment oftheir sick animals was satisfactory followed by (24.65%) good and (23.41%) poor.